THE EXPERIENCE OF NEW UZBEKISTAN IN DEVELOPING EFFECTIVE PUBLIC ADMINISTRATION (Global Conference on Multidisciplinary Research and Innovation, 2026)
Today, the ongoing fundamental reforms in our country are primarily aimed at the development of effective public administration. In particular, the rapid pace of global competition and technological advancement requires state institutions to be efficient, fast, and transparent. As noted by the President of the Republic of Uzbekistan, Shavkat Mirziyoyev, “without reforming the system of public administration, it is impossible to build a New Uzbekistan.”
Keywords: constitutional reforms, intersectoral regulatory harmonization, and integration into international legal standards